Development and Field Testing of a MALL for Filipino with a Reusable Framework for Mobile-Based Drills - Agapito, Jenilyn (Archīum Ateneo, 2020)
This paper describes the development and field testing of Ibigkas! Filipino, a mobile game that exercises learners’ fluency in identifying synonyms (kasingkahulugan) and antonyms (kasalungat) in the Filipino language. Twenty-four students from Grades 4, 5, and 6 were invited to play and answer comprehension tests to determine whether the game helped them improve their understanding of the content. Self-report questionnaires assessed the extent to which they enjoyed it. Additionally, three teachers were invited to a focus group discussion (FGD) to gather their insights about the game and how they may use it in their classes. Self-report feedback from students showed the game was fun, interesting, and sufficiently challenging. A significant increase in the post-test comprehension scores of the Grade 4 participants was found. This shows the potential of the game to make learning fun while helping realize learning goals. Teachers indicated they can use the game to supplement their Filipino classes and that the students will be receptive to the idea of utilizing a game for learning.